A meta-analysis of co-occurrence of non-suicidal self-injury and suicide attempt: Implications for clinical intervention and future diagnosis - Ye, Zhiyu; Xiong, Fang; Li, Wentian (Frontiers in Psychiatry, 2022)
BACKGROUND: Non-suicidal self-injury (NSSI) and suicide attempt (SA) are risk behaviors that lead to physical injury and even death in individuals, and are a very powerful risk factor when both occur together, with individuals presenting with more severe psychological and behavioral problems. Due to the different demographic characteristics of different study subjects, an overall understanding of the incidence and occurrence of this co-occurrence is lacking to clarify the focus of clinical interventions and future research directions. METHODS: A systematic search was conducted for relevant studies in English and Chinese that reported data on co-occurring non-suicidal self-injury and suicide attempts as of May 2022. The incidence of co-occurrence of non-suicidal self-injury and suicide attempt (NSSI+SA) was calculated using Stata version 16.0 software based on a random-effects model, and the differences in incidence in different populations were compared by subgroups of age group, comorbidity, and time of occurrence. The study was written in strict accordance with PRISMA norms and registration was completed on the PROSPERO platform (CRD42022329095). RESULTS: A total of 37 studies (139,573 individuals) were included for meta-analysis, and the combined incidence of non-suicidal self-injury and suicide attempt co-occurrence was 9.6%. Among different groups, the prevalence of NSSI+SA was 10%, 11%, 6%, and 26% in adolescents and young adults, adults, the general population, and people with mental illness, respectively, and the co-occurrence of NSSI+SA within 12 months was 17%. CONCLUSION: There is a significant group with a history of both non-suicidal self-injury and suicide attempts and presenting with more severe symptoms clinically. Targeted prevention and intervention are urgently needed, but the direction of intervention needs further research on the occurrence trajectory of this co-occurrence. Keywords: Non-suicidal self-injury, Suicide attempt, Co-occurrence